The Holistic Milieu - a Topic in Religion Education to Come? (Pedagogical Horizons, 2021)
The ‘world religions’-paradigm depicts the diversity of contemporary religion and worldviews only inadequately. Therefore, a new understanding of religion education needs to go beyond this form of thought. In particular, the entanglement of religion with other cultural areas deserves more focus. This includes the intersection of religiosity and self-help, also known as the ‘holistic milieu’. This paper argues why the holistic milieu should be included in the syllabus. It offers an overview of the field’s ideological, practical, and sociological features from the perspective of the study of religion. A concluding discussion sketches two approaches how the holistic milieu could be presented as a topic in religion-related classes.
Keywords: religious diversity; holistic milieu; self-help; spirituality; alternative therapies